Guidelines for creating a social network based on the Thailand tourism industry to develop sustainably - Yotkaew, Pramote (วารสารสันติศึกษาปริทรรศน์ มจร, 2018)
The purpose of this research was 1) Study on factors influence on the network participation, benefits, and cooperation in Thailand Tourism Society 2) Study on the problems, treats, and solution for creating the cooperation among private, social, and public sector base on basic Thai culture in developing sustainable Thailand’s tourism industry. 3) Setting the guideline for creating social network based on basic Thai culture in developing sustainable Thailand’s tourism industry. This applied research use mix-method. The result found that 1) the factors influence on the network participation, benefits, and cooperation in Thailand Tourism Society; the overview was very important . The key factors were community needs in art and traditional knowledge preserve, traditional culture, and Ethnicity identities. They was at very high level . The overview of the factors which correlated with network trust or cognitive on networks for developing the society tourism industry was middle positive correlation significantly at the .01 level. 2) The obstacle for forming network participatory is lack of knowledge in particular the leader must be sincere, strengthened, sacrificed, conscious mind, good coordinate to build community participation, and continue government cooperation. 3) The development of a Thai-based social network for the sustainable development of the tourism industry consists of four approaches: (1) Human development for network learning (2) network linkage and network involvement (3) friendship tourism linkage (4) network communication, benefit sharing, and public relation.